2007
DOI: 10.1186/ar2184
|View full text |Cite
|
Sign up to set email alerts
|

Association of cerebrospinal fluid anti-ribosomal P protein antibodies with diffuse psychiatric/neuropsychological syndromes in systemic lupus erythematosus

Abstract: We explored the relationship of antibodies to the whole ribosomal P proteins (P0, P1, and P2) in cerebrospinal fluid (CSF) with diffuse psychiatric/neuropsychological syndromes in systemic lupus erythematosus (SLE). CSF samples were obtained from 71 SLE patients (52 patients with diffuse psychiatric/neuropsychological syndromes [diffuse NP-SLE] and 19 patients with neurological syndromes or peripheral neuropathy [focal NP-SLE]) as well as from 24 patients with non-inflammatory neurological disease. Immunoglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 28 publications
3
46
1
Order By: Relevance
“…This result reinforces our hypothesis that antibody-mediated neuronal damage in SLE requires interruption of the BBB; as a validated measure of organ damage in SLE, most of which is mediated by circulating inflammatory cytokines or autoantibodies, the DI would not be expected to reflect damage in an organ protected by the BBB. This result is supported by previous studies that have reported correlations between NPSLE and antibrain antibodies or cytokines in cerebrospinal fluid, as opposed to peripheral blood (6)(7)(8)(9) and studies showing that the progression of cognitive impairment is independent of disease activity.…”
Section: Figuresupporting
confidence: 80%
See 1 more Smart Citation
“…This result reinforces our hypothesis that antibody-mediated neuronal damage in SLE requires interruption of the BBB; as a validated measure of organ damage in SLE, most of which is mediated by circulating inflammatory cytokines or autoantibodies, the DI would not be expected to reflect damage in an organ protected by the BBB. This result is supported by previous studies that have reported correlations between NPSLE and antibrain antibodies or cytokines in cerebrospinal fluid, as opposed to peripheral blood (6)(7)(8)(9) and studies showing that the progression of cognitive impairment is independent of disease activity.…”
Section: Figuresupporting
confidence: 80%
“…However, these mechanisms do not account for the majority of symptom complexes associated with NPSLE-in particular, the insidious cognitive decline manifested by up to 80% of lupus patients and the common mood disorders. Recent studies have demonstrated direct neurotoxic effects of lupus autoantibodies; antibodies to n-methyl-D-aspartate receptor (NMDAR), ribosomal P (anti-P), α-tubulin and phospholipid have been shown to bind neurons ex vivo with harmful effects (1)(2)(3)(4)(5) and all have been identified in the cerebrospinal fluid of SLE patients with CNS symptoms attributable to SLE (6)(7)(8)(9). In murine studies, circulating antibrain antibodies can cause neuronal dysfunction and apoptosis after breach of the BBB (5,(10)(11)(12), resulting in functional impairment on cognitive and behavioral tasks, as can antibodies directly injected intraventric- …”
Section: Introductionmentioning
confidence: 99%
“…Binding of ANAs to these proteins can generate immune complexes capable of triggering complement activation, eventually leading to extensive tissue inflammation. In addition to ANAs, anti-N-methyl-D aspartate receptor (anti-NMDAR) autoantibodies have also been associated with SLE and neuropsychiatric systemic lupus erythematosus (NPSLE) (Hanly et al, 2011;Hirohata, Arinuma, Takayama, & Yoshio, 2007;Yaniv et al, 2015;Yoshio, Hirata, Onda, Nara, & Minota, 2005). A study by DeGiorgio et al demonstrated cross-reactivity between the NR2A and NR2B subunits of NMDARs and antidouble-stranded (ds)DNA autoantibodies, leading to the loss of neurons both in vivo and in vitro models (DeGiorgio et al, 2001).…”
Section: Sle An Autoimmune Disease With Autoantibodies Directedmentioning
confidence: 95%
“…Recently, Hirohata et al [32] noted elevations in anti-ribosomal P levels with diffuse NPSLE, while others studies have demonstrated a more specific association with the NPSLE syndromes of psychosis and depression [24,26,27,33].…”
Section: Anti-ribosomal P (Anti-p) Antibodiesmentioning
confidence: 95%